The competitiveness os micro, small and medium sized companies in clusters - Dias, Reinaldo (Revista Hipótese, 2017)
This article analyzes the relation between the main macro phenomena of the end of the 20th century and start of the 21st, such as globalization and the scientific and technological revolution. The text addresses the productivity and competitiveness of Micro, Small and Medium sized companies in clusters; which are defined as groupings of sectoral companies that are geographically concentrated in determined territorial spaces - a concept defined by Michel Porter in the 90s, based on studies by other authors, in particular Alfred Marshall (1890), and italian intellectuals, like Beccatini and Garofalo.